Ecotoxicological effects of losartan on the brown mussel Perna perna and its occurrence in seawater from Santos Bay (Brazil) - Cortez, Fernando Sanzi [UNESP]; Souza, Lorena da Silva; Guimarães, Luciana Lopes; Almeida, João Emanoel; Pusceddu, Fabio Hermes; Maranho, Luciane Alves [UNESP]; Mota, Luciana Gonçalves; Nobre, Caio Rodrigues [UNESP]; Moreno, Beatriz Barbosa; Abessa, Denis Moledo de Souza [UNESP]; Cesar, Augusto; Santos, Aldo Ramos; et al. (Elsevier, 2018)
The antihypertensive losartan (LOS) has been detected in wastewater and environmental matrices, however further studies focused on assessing the ecotoxicological effects on aquatic ecosystems are necessary. Considering the intensive use of this pharmaceutical and its discharges into coastal zones, our study aimed to determine the environmental concentrations of LOS in seawater, as well as to assess the biological effects of LOS on the marine bivalve Perna perna. For this purpose, fertilization rate and embryolarval development were evaluated through standardized assays. Phase I (ethoxyresorufin O‑deethylase EROD and dibenzylfluorescein dealkylase DBF) and II (glutathione S-transferase GST) enzymes, glutathione peroxidase (GPx), Cholinesterase (ChE), lipoperoxidation (LPO) and DNA damage were used to analyze sublethal responses in gills and digestive gland of adult individuals. Lysosomal membrane stability was also assessed in hemocytes. Our results showed the occurrence of LOS in 100% of the analyzed water samples located in Santos Bay, Sao Paulo, Brazil, in a range of 0.2 ng/L–8.7 ng/L. Effects on reproductive endpoints were observed after short-term exposure to concentrations up to 75 mg/L. Biomarker responses demonstrated the induction of CYP450 like activity and GST in mussel gills exposed to 300 and 3000 ng/L of LOS, respectively. GPx activity was also increased in concentration of exposure to 3000 ng/L of LOS. Cyto-genotoxic effects were found in gills and hemocytes exposed in concentrations up to 300 ng/L. These results highlighted the concern of introducing this class of contaminants into marine environments, and pointed out the need to include antihypertensive compounds in environmental monitoring programs.
Keywords: Antihypertensive; Ecotoxicology; Emerging contaminants; Pharmaceuticals; Seawater